DOES THE USE OF GREEN ENERGY AFFECT ECONOMIC GROWTH? EVIDENCE OF MODERATING THE ROLE OF GOVERNANCE QUALITY IN BRICS - Muqdad Zaki Hammed Banana (Scholar Express Journals, 2024)
The influence of green energy consumption on the economic development of the BRICS nations—Brazil, Russia, India, China, and South Africa—is the subject of this research. The quality of governance is the primary concern. From 1990 to 2020, FM-OLS regression econometric modeling was used yearly for this aim. The findings indicate that the good governance index and green energy usage have a beneficial impact on economic development. Consequently, there is a positive and substantial relationship between green energy consumption (LREC) and economic growth; for every 1% rise in LREC, there is a 0.480% gain in economic growth. Economic growth is positively and significantly impacted by good governance (GGI), and for every unit rise in GGI, there will be a 1.991 unit gain in economic growth. According to the interpretation of the data from the other control variables in this research, economic growth would rise if there is a one percent increase in carbon dioxide emissions (LCO2), fossil fuel consumption (LFEC), gross fixed capital formation (LGFCF), inflation (LINFL), and trade openness (LTrade). (LTrade), there will be five different increases in economic growth: 0.639%, 0.018%, 0.141%, 0.205%, and 0.678%. The development of supportive policies, enhanced governance, suitable fiscal and tax frameworks, infrastructure development, international cooperation, education and awareness, research and development, promotion of foreign investment, increased coordination and collaboration between system components, and effective resource management are all areas that could use improvement, as these results demonstrate. Promote more excellent governance and the use of ecologically friendly energy to help the BRICS nations' economies flourish.
Keywords: Green Energy Consumption; Economic Growth; Good Governance